Asymmetric Double-Gate β-Ga2O3 Nanomembrane Field-Effect Transistor for Energy-Efficient Power Devices - Ma, Jiyeon; Cho, Hyung Jun; Heo, Junseok; Kim, Sunkook; Yoo, Geonwook (Advanced Electronic Materials, 2019)
The ultra-wide bandgap and cost-effective melt-growth of β-Ga2O3 ensure its advantages over other wide bandgap materials, and competitive electrical performance has been demonstrated in various device structures. In this paper, an asymmetric double-gate (ADG) β-Ga2O3 nanomembrane field-effect transistor (FET) comprised of a bottom-gate (BG) metal-oxide field-effect transistor and a top-gate (TG) metal-semiconductor field-effect transistor (MESFET) is demonstrated. Schottky contact properties are validated by characterizing the lateral Schottky barrier diode (SBD), which exhibits high rectification ratio and low ideality factor. The top-gate β-Ga2O3 MESFET shows reasonable electrical performance with a high breakdown voltage, as anticipated by three terminal off-state breakdown measurement. These properties are further enhanced by double-gate operation, and superior device performance is demonstrated; positive-shifted threshold voltage and reduced subthreshold slope enable the asymmetric double-gate β-Ga2O3 FET to operate at low power, and almost twice as much transconductance is demonstrated for high-frequency operation. These results show the great potential of asymmetric double-gate β-Ga2O3 FETs for energy-efficient high-voltage and -frequency devices with optimal material and structure co-designs.
Keywords: Asymmetric gates; Electrical performance; Gallium oxides; High frequency operation; Metal oxide field effect transistors; Schottky Barrier Diode(SBD); Schottky contact properties; Wide band-gap material; asymmetric-gate; beta-gallium oxide; metal-oxide field-effect transistor; metal-semiconductor field-effect transistor